Rescheduling sudden absences of nursing staff in hospital settings - Tuominen, Outi (fi=Turun yliopisto|en=University of Turku|, 2020)
The aim of this study is to evaluate the management of sudden absences of nursing staff in hospital settings. In addition, this study aims to describe nurse managers’ daily work regarding rescheduling due to sudden absences of nursing staff, from the perspectives of using a paper-based system or an IT-based rescheduling solution. The dissertation also includes an analysis of experiences of nursing staff floating. In Phase I, a scoping review was carried out to identify the IT-based rescheduling solutions for the daily rescheduling of nursing staff in a hospital setting, and rescheduling outcomes for patients, nursing staff and originations. In Phase II, a developed IT-based rescheduling solution was implemented at one university hospital department and a quasi-experimental pre- and post-test design was used to evaluate the nurse managers’ (n=17) work tasks with the Rescheduling Task Survey (RTS) during the rescheduling process of nursing staff. The quasi-experimental pre- and post-test design was repeated with a large sample of nurse managers (n=61), and the duration of the rescheduling process was observed. The usability of the IT-based rescheduling solution was evaluated with the System Usability Scale (SUS). In Phase III, the associations between stress, psychosocial factors and floating experience among nursing staff (n=1336) was evaluated, and the experiences nursing staff (n=747) with floating shifts during the past year were described. There is limited research on IT-based rescheduling staffing solutions and their outcomes for nursing staff, organizations and patients. Before and after implementation, the IT-based rescheduling solution nurse managers reported a total of 2,612 sudden absences with 5,800 rescheduling tasks such as phone calls and conversations. The main reason for sudden absence was unplanned sick leave (79%). After the implementation of the IT-based rescheduling solution, nurse managers’ rescheduling tasks, unstaffed and unplanned shift changes, the use of float pool nurses and floating nurses increased significantly. The implementation of the IT-based rescheduling process also revealed significant cost saving opportunities for hospitals. During this study’s short follow-up period, altogether €31,878 was saved with the use of floating nurses to cover sudden absences. There are no previous studies investigating floating and its association with stress among nursing staff. In this study, reported experience of stress did not differ significantly between participants with or without floating experience. However, there are factors related to floating that increase stress among nurses. Nurse managers need to ensure clear instructions for floating shifts on their units and that those instructions are followed.

Hoitohenkilökunnan äkillisten poissaolojen hallinta sairaaloissa Tämän tutkimuksen tarkoituksena oli analysoida hoitotyön esimiesten päivittäiseen resursointiin liittyvää työtä, heidän korvatessaan hoitajien äkillisiä poissaoloja. Päivittäisen resursoinnin prosessia tutkittiin ennen ja jälkeen sähköisen resursointisovelluksen käyttöönottoa. Lisäksi kartoitettiin hoitohenkilökunnan kokemuksia koetusta stressistä sekä tehdyistä lainavuoroista. Lainavuoroilla tässä tutkimuksessa tarkoitetaan työvuoroa, jossa hoitaja siirtyy tilapäisesti toiseen yksikköön tekemään suunnitellun työvuoronsa, mikäli oman yksikön tilanne sen sallii. Tämä tutkimus toteutettiin kolmessa vaiheessa. Tutkimuksen ensimmäisessä vaiheessa toteutettiin kirjallisuuskatsaus, jonka avulla kartoitettiin päivittäiseen resursointiin soveltuvia sovelluksia sekä päivittäisen resursoinnin seurauksia potilaalle, hoitohenkilökunnalle ja organisaatiolle. Toisessa vaiheessa implementoitiin kehitetty päivittäisen resursoinnin sovellus yhden yliopistollisen sairaalan toimialueelle. Lisäksi hoitotyön lähijohtajien (n=17) käyttämiä työsuoritteita arvioitiin ennen ja jälkeen päivittäiseen resursointiin tarkoitetun sovelluksen käyttöönottoa. Tutkimus toistettiin suuremmalla otoksella (n=61), lisäksi työsuoritteiden ajallinen kesto arvioitiin havainnoinnin avulla sekä päivittäisen resursoinnin sovelluksen käytettävyys arvioitiin. Tutkimuksen kolmannessa vaiheessa tutkittiin hoitajien (n=1336) koetun stressin, työn psyykkisten ja sosiaalisten tekijöiden sekä lainavuorokokemusten välistä yhteyttä. Tutkimustulokset osoittivat, että päivittäiseen resursointiin soveltuvia järjestelmiä on kuvattu vähän ja tietoa päivittäisen resursoinnin seurauksista on saatavilla rajoitetusti, erityisesti potilaiden näkökulmasta. Tässä tutkimuksessa hoitotyön esimiehet raportoivat yhteensä 2612 äkillistä poissaoloa, joiden pääasiallinen syy oli äkillinen sairausloma (79 %). Työsuoritteita, esim. puhelu tai keskustelu, raportoitiin yhteensä 5800. Päivittäiseen resursointiin tarkoitetun sovelluksen käyttöönoton jälkeen esimiesten työsuoritteet vähenivät merkitsevästi, kuin myös aliresursoidut työvuorot ja hoitohenkilökunnan äkilliset työvuorojen vaihdot. Myös vara- ja lainahenkilöstön käyttö tehostui. Sovelluksen käyttöönotto toi sairaaloille myös kustannussäästöjä; seuranta-ajan (neljä viikkoa) aikana kustannussäästöjä syntyi yhteensä 31 878 euroa. Tämän tutkimuksen mukaan lainavuorokokemus ei lisännyt hoitajien kokemaa stressiä. Sen sijaan lainavuoroon liittyy tekijöitä, jotka stressaavat hoitajia. Hoitotyön esimiesten tulee varmistaa, että lainavuoromallille on laadittu selkeät ohjeet, joita yksiköissä noudatetaan.